Solvothermal Synthesis of LaF3:Ce Nanoparticles for Use in Medicine: Luminescence, Morphology and Surface Properties - Anastasiia Dorokhina; Ryoya Ishihara; Hiroko Kominami; Vadim Bakhmetyev; Maxim Sychov; Toru Aoki; Hisashi Morii (Ceramics, 2023)
A series of LaF3:Ce3+ phosphors for application in photodynamic therapy are synthesized using a one-stage solvothermal synthesis. The synthesis conditions; type and quantity of stabilizer; concentration of activator providing the maximum intensity of UV- and X-ray-excited luminescence; lowest size; and highest colloidal stability of the phosphor nanoparticles are found. As a result of this study, the following parameters are determined using cerium content 5% mol. ethanol as the reaction medium for the solvothermal synthesis and polyvinylpyrrolidone as the stabilizer at an optimized amount.